Environmental awareness and attitude among Iranian students in Malaysian universities - Z., Aminrad; Muda, Azizi; Abd Wahab, Mahdi; Harun, Rosta; Nawawi, Mokhtar (Thai Society of Higher Eduction Institutes on Environment, 2010)
This study focuses on environmental awareness and attitude among Iranian students in Malaysian universities. It evaluates the awareness and attitude of a group of 541 from 14 universities. The figure to 541 is considered the representative of these students and the selection was based on Stratified Random sampling method and G-power soft ware. A set of questionnaire which comprised of 25 questions was applied as instrument for data collection. The results revealed that environmental awareness was overall moderate while environmental attitude was high. The study also found that there was no significant difference observed between sex groups while environmental awareness results indicated that there were significant difference among different levels of education. This trend was in contrast with observation for environment alattitude status. The age groups analysis results revealed significant difference in environmental awareness and attitude. It was also found that the media positively affected the level of environmental awareness and attitude among students. The study concluded that increase on age and level of education would improve the level of awareness and attitude regarding to environmental issues.